2022
DOI: 10.3389/fonc.2022.882784
|View full text |Cite
|
Sign up to set email alerts
|

Salvia chinensis Benth Inhibits Triple-Negative Breast Cancer Progression by Inducing the DNA Damage Pathway

Abstract: ObjectiveTriple-negative breast cancer (TNBC) is distinguished by early recurrence and metastases, a high proclivity for treatment resistance, and a lack of targeted medicines, highlighting the importance of developing innovative therapeutic techniques. Salvia chinensis Benth (SCH) has been widely studied for its anticancer properties in a variety of cancers. However, its significance in TNBC treatment is rarely discussed. Our study investigated the anticancer effect of SCH on TNBC and the underlying mechanism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“… 19 In addition, beta-sitosterol affects several cell signaling pathways, including the cell cycle, proliferation, angiogenesis, apoptosis, and anticancer pathways, especially in TNBC cells. 20 , 21 These findings suggest that these components may be critical for the therapeutic effects of CSSGF.…”
Section: Discussionmentioning
confidence: 89%
“… 19 In addition, beta-sitosterol affects several cell signaling pathways, including the cell cycle, proliferation, angiogenesis, apoptosis, and anticancer pathways, especially in TNBC cells. 20 , 21 These findings suggest that these components may be critical for the therapeutic effects of CSSGF.…”
Section: Discussionmentioning
confidence: 89%
“…Compound 5 is a commonly occurring phytosterol called β-sitosterol, which is a key component present in plants. Out of the many pharmacological and biological effects that have been reported for this compound over the past decades, anti-inflammatory, angiogenic, antiadipogenic, anti-diabetic, anti-oxidant, anti-cancer, immunomodulatory activities and a role in cardiovascular diseases prevention can be mentioned, reported from recent findings that can be beneficial in drug developments and other therapeutic applications [45][46][47][48][49][50][51]. The hypocholesterolemic effects of E. hirta and its role in curing obesity have been linked to this natural compound [22], as well as the larvicidal activity of E. thymifolia [21].…”
Section: Discussionmentioning
confidence: 99%
“…[ 6 ] Furthermore, Wang et al found that SJC aqueous extract inhibits the occurrence and development of triple-negative breast cancer through DNA damage-related pathways. [ 7 ] Various studies have reported the anti-CRC effects of the primary components of Salvia chinensis Benth , such as Ursolic acid, quercetin, and resveratrol. For instance, Ursolic acid has been documented to induce apoptosis and modulate autophagy in apoptosis-resistant CRC cells via the JNK pathway.…”
Section: Introductionmentioning
confidence: 99%